Analisis Kemampuan Pemahaman Konsep Siswa Kelas VIII SMP Citra Dharma Jakarta Pada Materi Pythagoras Dan Statistika - Destiana Anugrah Putri; Indah Rusmarhadi; Karisma Agustia; Nestiana Juin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to analyze the level of mathematical concept understanding among eighth-grade junior high school students, with a focus on Pythagoras and Statistics. The research method employs a qualitative approach, involving students as research subjects. Research instruments include concept understanding tests, classroom observations, and student interviews. Data analysis is conducted by identifying the level of students' mathematical concept understanding, the factors influencing such understanding, and a comparison between Pythagoras and Statistics. The research results are expected to provide a profound understanding of the extent to which eighth-grade junior high school students comprehend these mathematical concepts. This study can significantly contribute to the improvement of teaching and learning mathematics at the junior high school level. Findings from the analysis of mathematical concept understanding can assist teachers in designing more effective and comprehensive teaching strategies, as well as provide information for the development of a curriculum that better aligns with students' needs in understanding mathematical concepts.